Driving sustainable development in South Asia: unleashing the power of microfinance and ICT - Tang, Xiang Hua; Bani, Yasmin; Abdul Samad, Abdul Rahim; Ibrahim, Saifuzzaman (Autonomous University of Madrid, 2023)
This study examines the impact of Information and Communication Technology (ICT) and Microfinance Institutions (MFIs) on sustainable development in South Asian countries. ICT can help reduce financial barriers and improve the efficient allocation of financial resources by enhancing information access for the poor. Additionally, MFIs provide sustainable economic opportunities for the impoverished, fostering inclusive growth and reducing poverty in the region. The aim of this paper is to analyze the threshold effects of ICT on MFIs and sustainable development using a threshold regression and system GMM. Furthermore, by introducing the interaction term between MFIs and ICT, this study offers a new perspective on analyzing the key factors influencing sustainable development. The empirical results indicate that there is indeed a non-linear relationship between MFIs and sustainable development, with ICT as the threshold variable. Moreover, the interaction between ICT and MFIs significantly promotes the level of sustainable development in South Asia. The empirical findings underscore the importance of further leveraging the advantages of microfinance and ICT to effectively drive high-quality socio-economic development in the South Asian region. Therefore, it is recommended that relevant policies be implemented in South Asia to support and encourage the widespread adoption of ICT and microfinance in impoverished areas, thus aiding in the improvement of living standards and environmental conditions for the poor.